Existence of Antibiotics in Stalls at Jatiroke Village, Jatinangor Sub District - Jaelani, Elan; Istriati, Istriati; Sunjaya, Deni Kurniadi (Althea Medical Journal, 2016)
Background: Improper use of antibiotics can lead to lack of drug efficacy against bacteria, and cause resistanceÂ to the antibiotics itself. Antibiotics are classified into prescription drugs that should not be available overÂ the counter because of its dangerous effect. It is important to study the presence of antibiotics in traditionalÂ stalls. Objective of this study was to investigate existence of antibiotics in stalls, and to investigate reasonsÂ of stall- owners for selling antibiotics.Methods: This study used mixed method design, and sequential explanatory approach, and conductedÂ direct observation, spatial mapping, and interview with stall-owners selling drugs in Jatiroke village,Â Jatinangor sub district from September to November 2013. Total sampling was conducted in this study.Results: Fifty percent from 24 surveyed stalls sold Antibiotics Amoxicillin. The map showed stalls sellingÂ antibiotics at roadside. Amoxicillin sold package with Dexamethasone and Non-Steroid Anti InflammatoryÂ Drugs (NSAID) was soldby several stalls. Shopkeepers sold antibiotics due to lack of knowledge about thedrug, need for self-medication, demand, and availability of drugs supply.Conclusions: Antibiotics can be found in several stalls in Jatiroke village, and improper of use of this drug canÂ lead to resistance and less efficacy for treating infections. Although the Act for prescription drugs still exists,Â low of monitoring and enforcement the regulation by the Badan Pengawas Obat dan Makanan (BPOM) mayÂ be one of many factors that influence the existence of antibiotics in the stalls. [AMJ.2016;3(2):239â43]DOI:Â 10.15850/amj.v3n2.779